PENINGKATAN UJI FISIS KULIT DOMBA GOLF GLOVE PEARL WHITE DENGAN PENAMBAHAN KONSENTRASI PERAMIT LSW NEW PADA PROSES FATLIQUORING - Diana Nur Kholida; R.L.M Satrio Ari Wibowo; Entien Darmawati (Politeknik ATK Yogyakarta, 2019)
This study aims to explain the increase of physical test of golf glove pearl white sheepskin with the addition of the concentration of the Peramit LSW New. The research was conducted in February to April 2019 in the CV Sari Banteng Mulya. The material used was wet blue sheepskin with R quality of 5 pieces and shaving thickness 0,4-0,45 mm . The auxiliary materials used in the fatliquoring process were Pelastol ET, Pellan 802, Pellan L-90, Peramit LSW New, and Peramit MLN. The method used in the fatliquoring process was a short float. The result of the study obtained the concentration of Peramit LSW New of 2.5% in the fatliquoring process for improving the tear strength quality of golf glove pearl white sheepskin. Result of physical testing tensile strength, elongation, and tear strength was increased. Tensile strength test result from 174 Kg/cm2 to 286,5 Kg/cm2, elongation from 81,804% to 86,56%, and ter strength from 16,93 Kg/cm to 31,2 Kg/cm. Peramit LSW New can improve the t physical test quality of glove skin so that it can be used as a raw material for golf glove pearl white.